Pemanfaatan Batu Sungai Laeya Kabupaten Konawe Selatan untuk Stone Matrix Asphalt Kasar - Rahmat Palebangan; Alpius; Elizabeth (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
In general, roads in Indonesia use several mixtures in their processing, such as stone matrix asphalt or also known as split mastix asphalt (SMA), namely hot mix asphalt concrete which maximizes the use of coarse aggregate and asphalt as a binder. This research is intended to utilize Laeya river stone in South Konawe Regency in a Coarse stone matrix asphalt (SMA) mixture. The method used in this research is to test the characteristics of the aggregate and then design the composition of the stone matrix asphalt (SMA) mixture as well as the conventional Marshall test and the Marshall immersion test. The research results concluded that the aggregate originating from the Laeya river met the requirements as a material used in road pavement. From the results of the conventional marshall test using asphalt content of 6.00%, 6.25%, 6.50%, 6.75%, 7.00% the values ​​for stability, VIM, flow, VMA were obtained which met the general specifications of the 2018 Highways. From the marshall immersion test the residual marshall stability value was obtained at 96.30% with an asphalt content of 7.00% and met predetermined standards, namely at least > 90%